Housewife perception of gadget functions: Economy creative opportunity in woman empowerment, theory of economic sociology perspective - Gani, Irwan; Suharnanik, Suharnanik (Bulletin of Social Informatics Theory and Application, 2021)
Women as housewives can provide various responses to the existence of gadgets or better known as gadgets. With her limitations as a woman who focuses on household functions, she is still able to respond to some advances in gadget functions. The longer the function of the gadget, the more sophisticated it causes changes in behavior that are different from before, sometimes even confusing in determining good attitudes and behavior according to them. The value of multiple and not absolute behavior due to changes in the function of gadgets causes housewives to reject the latest gadgets because they harm the behavior and values they believe in. This research was conducted on several housewives. Data was collected using a qualitative approach, through interviews and direct observation of housewives. The data were analyzed using a descriptive study of modern socio-economic theory to see how housewives respond to the development of gadgets. The results showed that housewives had excessive concerns about the progress of gadgets, so they tended to reject these advances. More relented to have the latest gadgets, and do not know how to use gadgets in order to take opportunities in empowering the creative economy. This study uses an economic sociology study, to be able to provide a more comprehensive analysis in looking at the phenomenon of housewives in urban areas.